OIL PRICES AND THEIR LONG-TERM RELATIONSHIP WITH MACROECONOMIC AND FINANCIAL INDICATORS - Vesna Bucevska; Borjan Gjelevski; Lea Matevska (Economic Review, 2023)
The objective of this paper is to find out whether there is a long-term relationship or in other words cointegration, between the prices of oil futures and the following factors: the consumer price index (CPI), the exchange rate of the USD to the EUR, the prices of gold, and the price of Bitcoin. This research was conducted using monthly data, extracted from both Refinitiv and Yahoo Finance, in the period 2014-2022. In order to find the cointegrating relationship between the above mentioned variables, the Johansen test was used, after which, the Vector Error Correction Model (VECM) system was composed to formulate a set of equations that explain all the variables. The results of this research show that only one cointegrating relationship exists between the previously mentioned variables. Namely, in a state of long-term equilibrium, only the prices of gold have a statistically significant effect on oil prices.